PREPARATION, CHARACTERIZATION AND STABILITY STUDIES OF SOLID SELF EMULSIFYING DRUG DELIVERY SYSTEM OF NIFEDIPINE - BINDHANI, SABITRI; MOHAPATRA, SNEHAMAYEE; KAR, RAJAT KUMAR (International Journal of Applied Pharmaceutics, 2020)
Objective: The objective of this work was to improve the solubility and dissolution rate of Nifedipine by preparing a solid-self micro emulsifying drug delivery system (Solid-smedds). Methods: Liquid-self-emulsifying drug delivery system formulations were prepared by using linseed oil as oil, tween 80 as a surfactant and PEG 400 as cosurfactant. Components were selected by solubility screening studies and the self-emulsifying region was identified by the pseudo-ternary phase diagram. Thermodynamic stability study was performed for the determination of stable liquid-smedds formulation. These formulations were evaluated for self-emulsification time, drug content analysis, robustness to dilution test, particle size analysis, in vitro diffusion study, and Stability study. Solid self-micro emulsifying formulations were prepared by using aerosil-200 at a different ratio. Lf9S (0.65:1) was selected due to its highest drug entrapment efficiency and a decrease in particle size. It was selected for further studies into DSC, SEM, FTIR, and XRD analysis. Results: DSC and XRD result shows that the drug within the formulation was in the amorphous state. From the SEM study, it was observed that the drug has been uniformly distributed and having a smooth surface. From the in vitro dissolution study, it improved the dissolution rate of nifedipine which was 98.70% of drug release where pure drug release only 6.72%. Conclusion: In conclusion, a solid self-micro emulsifying drug delivery system is improved the solubility and drug release rate but also improved the stability of the formulation.